Effective density and metals content of particle emissions generated by a diesel engine operating under different marine fuels. (January 2021) - Momenimovahed, Ali; Gagné, Stéphanie; Gajdosechova, Zuzana; Corbin, Joel C.; Smallwood, Gregory J.; Mester, Zoltan; Behrends, Brigitte; Wichmann, Volker; Thomson, Kevin A.
Abstract: A differential mobility analyzer along with a centrifugal particle mass analyzer was employed to study the effect of fuel type on effective density for nascent and non-volatile particles generated by a marine diesel engine. The engine was operated at 1500 rpm at loads between 10% and 100%. Three different fuels were evaluated: diesel fuel, distillate marine oil Grade A, and intermediate fuel oil. A combination of a thermodenuder and a catalytic stripper was used to remove semi-volatile materials in order to measure the denuded particulate effective densities. Particle mass concentrations were quantified using thermal-optical analysis as well as integrated particle size distribution. Relatively good agreement between IPSD and TOA was observed for undenuded particle mass concentrations, however IPSD underestimated the mass concentrations measured for denuded particles by approximately 76%. The results revealed that more than 93% of undenuded particles from diesel and DM-A fuels were composed of semi-volatile materials. The denuded effective density values at some test conditions were significantly higher than the effective density of soot particle from other sources specifically for particles smaller than 100 nm generated from IFO. We hypothesized that the high effective density values are in part due to large proportion of metal-containing tarballs. By comparing the measured effective densities with a literature effective density function for soot, we were able to predict the metal mass concentrations measured by ICP-MS with reasonable accuracy in most cases. Highlights: The effect of fuel type on effective density and metals content of particles from a marine diesel engine is studied. Particulate emissions generated from IFO were composed of significant amount of heavy elements including S, V, Ni and Fe. For the case of diesel and DM-A, more Ca, Zn, S and P were observed specifically at 100% engine load. Heavy elements in the IFO fuel significantly increase the particle effective density.